Effects of Atrial Ischemia on Left Atrial Remodeling in Patients with ST-Segment Elevation Myocardial Infarction - Montero-Cabezas Jose M; Abou Rachid; Chimed Surenjav; Fortuni Federico; Goedemans Laurien; Ajmone Marsan Nina; Bax Jeroen J; Delgado Victoria (Elsevier, 2022)
BACKGROUND
Adverse left atrial (LA) remodeling after ST-segment elevation myocardial infarction (STEMI) has been associated with poor prognosis. Flow impairment in the dominant coronary atrial branch (CAB) may affect large areas of LA myocardium, potentially leading to adverse LA remodeling during follow-up. The aim of this study was to assess echocardiographic LA remodeling in patients with STEMI with impaired coronary flow in the dominant CAB.
Methods
Of 897 patients with STEMI, 69 patients (mean age, 62 ± 11 years; 83% men) with impaired coronary flow in the dominant CAB (defined as Thrombolysis In Myocardial Infarction flow grade < 3) were retrospectively compared with an age- and sex-matched control group of 138 patients with normal dominant CAB coronary flow.
Results
Patients with dominant CAB-impaired flow had higher peak troponin T (3.9 μg/L [interquartile range, 2.2-8.2 μg/L] vs 3.2 μg/L [interquartile range, 1.5-5.6 μg/L], P = .009). No differences in left ventricular ejection fraction or mitral regurgitation were observed between groups at baseline or at follow-up. LA remodeling assessment included maximum LA volume, speckle-tracking echocardiography-derived LA strain, and total atrial conduction time assessed on Doppler tissue imaging at baseline, 6 months, and 12 months. Patients with dominant CAB-impaired flow presented larger LA maximal volumes (26.9 ± 10.9 vs 18.1 ± 7.1 mL/m2, P < .001) and longer total atrial conduction time (150 ± 23 vs 124 ± 22 msec, P < .001) at 6 months, remaining unchanged at 12 months. However, all LA strain parameters were significantly lower from baseline (reservoir, 20.3 ± 10.1% vs 27.1 ± 14.5% [P < .001]; conduit, 9.1 ± 5.6% vs 12.8 ± 8% [P < .001]; booster, 9.1 ± 5.6% vs 12.8 ± 8% [P < .001]), these differences being sustained at 6- and 12-month follow-up.
Conclusions
Atrial ischemia resulting from impaired coronary flow in the dominant CAB in patients with STEMI is associated with LA adverse anatomic and functional remodeling. Reduced LA strain preceded LA anatomic remodeling in early phases after STEMI.